Law students' descriptions of legal reasoning. Issue 4 (2nd October 2022) - Haarala-Muhonen, Anne; Hyytinen, Heidi; Tuononen, Tarja; Melander, Sakari
ABSTRACT: This study is an exploration of bachelor-level law students' descriptions of legal reasoning in a large multidisciplinary university in Finland. Thirty students participated in this qualitative study. The participants comprised three student groups: first-year students (n = 10), second-year students (n = 10) and third-year students (n = 10). The data were first collected via semi-structured interviews and then analysed by using qualitative content analysis. The results revealed variation in students' descriptions of legal reasoning. Most shared the view that legal reasoning comprised legal knowledge. However, some students emphasised the view that legal reasoning includes both skills and a certain mindset to use legal knowledge. The students' descriptions of legal reasoning varied between the student groups. The third-year students were more often able to provide detailed and coherent perceptions of their legal reasoning than the first- and second-year students. The conceptions bear consequences for the learning processes. Thus, the results imply that the development of legal reasoning needs to be facilitated systematically during university studies.